JURISPRUDENCE AND ITS ROLE IN THE TRAINING OF JURIST PERSONNEL (American Journal of Pedagogical and Educational Research, 2023)
This article will analyze the most important issues related to the development of the state language in Uzbekistan. In particular, the formation and progress of the science of jurisprudence in the introduction of the state language in Uzbekistan is studied. Foreign experiments in this area will be studied and proposals and recommendations will be made to introduce them into the system of Science of Uzbekistan.